The GAMIFICATION DEVELOPMENTS IN EDUCATION: PERKEMBANGAN GAMIFIKASI DI BIDANG PENDIDIKAN - Yerry Soepriyanto; Aris Triwahyu Febriansah; Syaifuddin, Aris (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
Gamification is an emerging trend in many sectors and is being adopted in many different contexts for a variety of purposes. Gamification has the potential to increase motivation, participation, and social influence among its users. In education, it has proven to be effective in increasing student interest in learning, as well as providing challenges that can improve the quality of learning materials. The incorporation of gamification elements in learning has been shown to positively impact learners by fostering motivation, engagement, skill development, and a sense of achievement, thereby enhancing the overall learning experience. This article aims to outline the growth of gamification implementation in Indonesia, both conceptually and empirically in education. It is important to map the application of gamification in Indonesia that is published in journals published in Indonesia. The method used in this research was the Systematic Literature Review, the data was obtained from the publication portal site gerba digital reference (Garuda) with the keyword of "gamification" during 2018-2022, and analyzed using the SLR method as described by Kitchenham and Charters. The findings of this study state that there has been an increase in the use of gamification during the Covid-19 pandemic. Higher education is the level of education that uses the most gamification approaches in learning activities. Points and leaderboards are the most widely used elements to motivate and increase learner engagement. Gamification is proven to make the learning environment more interactive.